Protein palmitoylation plays an important role in Trichomonas vaginalis adherence - Nievas, Yésica Romina (2018)
The flagellated protozoan parasite Trichomonas vaginalis is the etiologic agent of trichomoniasis, the most common non-viral sexually transmitted infection worldwide. As an obligate extracellular pathogen, adherence to epithelial cells is critical for parasite survival within the human host and a better understanding of this process is a prerequisite for the development of therapies to combat infection. In this sense, recent work has shown S-acylation as a key modification that regulates pathogenesis in different protozoan parasites. However, there are no reports indicating whether this post-translational modification is a mechanism operating in T. vaginalis. In order to study the extent and function of S-acylation in T. vaginalis biology, we undertook a proteomic study to profile the full scope of S-acylated proteins in this parasite and reported the identification of 363 proteins involved in a variety of biological processes such as protein transport, pathogenesis related and signaling, among others. Importantly, treatment of parasites with the palmitoylation inhibitor 2-bromopalmitate causes a significant decrease in parasite: Parasite aggregation as well as adherence to host cells suggesting that palmitoylation could be modifying proteins that are key regulators of Trichomonas vaginalis pathogenesis.